Poverty Dynamics of Nepal: A Comparative Analysis of Multidimensional Poverty Reports (2018-2025) - BaidhyaTamang, Santosh Kumar (Medha: A Multidisciplinary Journal, 2026)
This paper aims to analyze the poverty dynamics of Nepal by comparing data from two different multidimensional country poverty reports (2018 and 2021) and the global Multidimensional Poverty Index (MPI) country briefing report 2025 Nepal. By assessing the changes in poverty measures under three dimensions—education, health, and standard of living—over these periods, we have gained insights into the progress and challenges faced by Nepal in addressing poverty. Similarly, the 2021 report also started to address the age group, children, and persons with disabilities’ poverty level, which is noteworthy for the policymakers and planners. Overall, MPI decreased dramatically between the 2018 and 2021 reporting periods, from 0.133 to 0.074, but it grew marginally (0.085) in the 2025 reporting period compared to the 2021 period. This indicates that the multidimensionally poor population under the 2021 reporting period is, on average, less deprived than the multidimensionally poor population under the 2018 reporting period; however, the average level of deprivation in 2025 is somewhat higher than that of the 2021 reporting period.